Thermal expansion coefficient and dielectric properties of non-stoichiometric cordierite compositions with excess MgO mole ratio synthesized from mainly kaolin and talc by the glass crystallization method - Banjuraizah, Johar; Hasmaliza, Mohamad; Zainal Arifin, Ahmad (Elsevier B. V., 2010)
Link to publisher's homepage at http://www.sciencedirect.com/